Abatement of CH4 emitted by CNG vehicles using Pd-SBA-15 and Pd-KIT-6 catalysts. (1st June 2015) - Hussain, M.; Deorsola, F.A.; Russo, N.; Fino, D.; Pirone, R.
Highlights: Different mesoporous silica supported Pd catalysts were tested for CH4 catalytic oxidation. Mesoporous silica supported Pd catalysts were synthesized and characterized. Pd addition did not affect the structure and textural properties of the supports. All catalysts were allowed to reach complete CH4 conversion at 750 °C. Higher Pd loadings enhanced the reaction rate, with conversion at less than 450 °C. Abstract: Compressed Natural Gas (CNG) engines are growing in interest in the car market due to their ability in the limitation of NOx and CO2 emissions. Unburned methane is harder to oxidize than gasoline-derived unconverted HCs and its strong greenhouse effect induces the development of tailored after treatment technologies. In this work, SBA-15 and in particular KIT-6 have been used as supports for Pd catalysts for the abatement of methane emitted by CNG engines. The synthesized materials have been characterized through XRD, N2 -adsorption/desorption, EDX, STEM, and TEM analysis techniques. The influence of different pore structure and size of the mesoporous supports as well as of different Pd loading (in the range 0.25–0.7 wt%) on the activity has been investigated. All mesoporous silica supported Pd catalysts showed almost complete conversion of methane, although catalysts with the lowest Pd loadings reached 90% of conversion over 650 °C, whereas the maximum Pd loadings allowed to decrease the temperature of complete conversion, with T 90 at 405 °C by employing the KIT-6 mesoporous silica support.